Rabbits for food - Kirshenbaum, Binnie (Soho, 2019)
"Master of razor-edged literary humor Binnie Kirshenbaum returns with her first novel in a decade, a devastating, laugh-out-loud funny story of a writer's slide into depression and institutionalization. It's New Year's Eve, the holiday of forced fellowship, mandatory fun, and paper hats. While dining out with her husband and their friends, Kirshenbaum's protagonist--an acerbic, mordantly witty, and clinically depressed writer--fully unravels. Her breakdown lands her in the psych ward of a prestigious New York hospital where she refuses all modes of recommended treatment. Instead, she passes the time chronicling the lives of her fellow "lunatics" and writing a novel about how she got to this place. Her story is a hilarious and harrowing deep dive into the disordered mind of a woman who sees the world all too clearly. Propelled by stand-up comic timing and rife with pinpoint insights, Kirshenbaum examines what it means to be unloved and loved, to succeed and fail, to be at once impervious and raw. Rabbits for Food shows how art can lead us out of--or into--the depths of disconsolate loneliness and piercing grief. A bravura literary performance from one of our most witty and indispensable writers"--